Mean platelet volume and left ventricular geometry in patients with aortic valve stenosis. (17th November 2015) - Kurisu, Satoshi; Higaki, Tadanao; Ikenaga, Hiroki; Watanabe, Noriaki; Shimonaga, Takashi; Iwasaki, Toshitaka; Ishibashi, Ken; Dohi, Yoshihiro; Fukuda, Yukihiro; Kihara, Yasuki
Abstract: Background : Mean platelet volume (MPV) is a well-established marker of platelet activation. In the current study, we compared MPV between patients with aortic valve stenosis (AS) and control subjects. We also assessed the association between MPV and left ventricular geometry in patients with AS. Methods and results : The study population consisted of 75 patients with AS and 38 age- and sex-matched control subjects. In patients with AS, peak pressure gradient was 83.0 ± 30.8 mm Hg. MPV was significantly larger in patients with AS than control subjects (10.57 ± 1.05 fl versus 9.72 ± 0.66 fl, p < 0.001). There was a significant association between peak pressure gradient and MPV in 75 patients with AS and 38 control subjects ( r = 0.35, p < 0.001). Among the patients with AS, there were 12 patients with normal geometry, 10 patients with concentric remodeling, 14 patients with eccentric hypertrophy and 39 patients with concentric hypertrophy. There was no significant difference in MPV among the four groups. There was no significant association between MPV and LVM index. Conclusions : Our data suggested that MPV increased in patients with AS, but did not reflect left ventricular geometry.